The Maoist insurgency in Nepal: revolution in the twenty-first century - Lawoti, Mahendra; Pahari, Anup K. (Routledge contemporary South Asia series, 2010)
pt. 1. Introduction -- pt. 2. Agency, ideology, organization, and support -- pt. 3. Revolutionary governance -- pt. 4. Ethnic dimension -- pt. 5. Military and state dimension -- pt. 6. External dimension -- pt. 7. Identifying the causes -- pt. 8. After the war.
Keywords: Nepal -- Politics and government -- 1990-; Aufsatzsammlung; Partisanenkrieg; Nepal; Geschichte 1996-2006; Politischer Wandel; Soziale Bewegung; Guerilla; Maoismus; Bürgerkrieg in Nepal